Overview of the Guha method as a data mining technique - Todorovski, Viktor; CHorbev, Ivan; Loshkovska, Suzana (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2010)
This paper is concerned with current applications and researches of GUHA, a method for hypothesis generation. The GUHA method is very promising in the field of association rules data mining. Some of the current software implementations of the GUHA procedures offer simple mechanism of integration with BI processes, especially where large data sets are being processed. To use data for processing, it must first be pre-processed or aggregated and after that, as a data set to be used by the implementations of the GUHA procedures. The most preferred processing data representation are bit string cards of categories, mainly because logical operations can be easily performed on such representation of data. Since GUHA has a significant statistical and logical background it is taken as very relevant in positive and negative association rules mining, and also in interesting hypothesis discovery.